Respuesta :
Answer:
The rule is [tex]\implies f(n)=4n+1[/tex]
Step-by-step explanation:
The ordered for Larry's inputs and the corresponding outputs displayed by the calculator are:
(1, 5), (2, 9), (3, 13), (4, 17)
We use the y-values of the ordered pairs to obtain the rule.
The y-values are:
[tex]5,9,13,17[/tex]
The y-values form a sequence. The first term of this sequence is:
[tex]a=5[/tex]
The common difference of this sequence is
[tex]d=9-4=5[/tex]
The rule is given by:
[tex]f(n)=a+d(n-1)[/tex]
We substitute the values to obtain:
[tex]f(n)=5+4(n-1)[/tex]
[tex]\implies f(n)=5+4n-4[/tex]
The rule is [tex]\implies f(n)=4n+1[/tex]
Answer:
(C) f(n) = 4n + 1
Step-by-step explanation:
i just took the test